Social and Regional Disparities in Utilization of Maternal and Child Healthcare Services in India: A Study of the Post-National Health Mission Period - Bango, Madhumita; Ghosh, Soumitra (Frontiers in Pediatrics, 2022)
Background: Over the last two decades, India has enjoyed accelerated economic growth but has fared poorly in human development indicators and health outcomes. Significant health inequities and access to healthcare continue to exist and have widened across states and within communities. This study looks at the changes and disparities in maternal and child healthcare amongst disadvantaged and advanced social groups in three states of India. Data and Methods: Four rounds of National Family Health Survey data were used to measure IMR and U5MR according to the social groups for the selected states. The study investigates the socio-economic inequities manifested into caste, class and gender differentials and inequities in availability, utilisation and affordability of health services. Descriptive statistics and the logit regression model were used in the analyses. Individual and household-level covariates are used in the analyses. Results: The probability of not receiving full ANC or full immunization for the children was highest among SC/ST families, followed by economic class and mother’s education and residence. Tamil Nadu shows the highest utilization of public health facilities, while Bihar was the poorest in terms of health outcomes and utilization of MCH care services even after a pre-NHM period, along with Bihar and West Bengal shows a private healthcare dependence as well. Conclusions: The study detects the presence of significant caste/tribe differentials in the utilization of MCH care services in India. Limited accessibility and unavailability of complete healthcare are the foremost reasons for the under-utilization of these services, especially for the people from deprived social groups. Result also suggests it is critical to ensure health for all in the immediate future. It will be the effectiveness with which India addresses inequities in providing health services and assurance of quality care.